Computed Tomography Radiomics Kinetics as Early Imaging Correlates of Osteoradionecrosis in Oropharyngeal Cancer Patients - Barua, Souptik; Elhalawani, Hesham; Volpe, Stefania; Al Feghali, Karine A.; Yang, Pei; Ng, Sweet Ping; Elgohari, Baher; Granberry, Robin C.; Mackin, Dennis S.; Gunn, G. Brandon; Hutcheson, Katherine A.; Chambers, Mark S.; et al. (Frontiers in Artificial Intelligence, 2021)
Osteoradionecrosis (ORN) is a major side-effect of radiation therapy in oropharyngeal cancer (OPC) patients. In this study, we demonstrate that early prediction of ORN is possible by analyzing the temporal evolution of mandibular subvolumes receiving radiation. For our analysis, we use computed tomography (CT) scans from 21 OPC patients treated with Intensity Modulated Radiation Therapy (IMRT) with subsequent radiographically-proven ≥ grade II ORN, at three different time points: pre-IMRT, 2-months, and 6-months post-IMRT. For each patient, radiomic features were extracted from a mandibular subvolume that developed ORN and a control subvolume that received the same dose but did not develop ORN. We used a Multivariate Functional Principal Component Analysis (MFPCA) approach to characterize the temporal trajectories of these features. The proposed MFPCA model performs the best at classifying ORN vs Control subvolumes with an area under curve (AUC) = 0.74 (95% confidence interval (C.I.): 0.61-0.90), significantly outperforming existing approaches such as a pre-IMRT features model or a delta model based on changes at intermediate time points, i.e. at 2- and 6-month follow-up. This suggests that temporal trajectories of radiomics features derived from sequential pre- and post-RT CT scans can provide markers that are correlates of RT-induced mandibular injury, and consequently aid in earlier management of ORN.